Seasonal variation in fetal growth: Accounting for sociodemographic, biological, and environmental exposures - Pereira, Gavin; Cook, A.; Haggar, F.; Bower, C.; Nassar, N. (2012)
We sought to investigate seasonal variation in fetal growth, accounting for important sociodemographic, biological, and environmental exposures. Records of births 1998 through 2006 in Perth, Western Australia were obtained (N = 147,357). We investigated small for gestational age and sex and the proportion of optimal birthweight (POBW) in relation to seasonal exposures (season, temperature, sunlight) by trimester of pregnancy. Adjustment was made for a wide range of risk factors. The POBW for neonates with third trimesters predominantly in summer was 0.18% (0.00-0.36%) lower than for those in winter. POBW decreased by 0.14% (0.01-0.27%) per interquartile range increase in third-trimester temperature (9.15°C). An interquartile range increase in temperature over pregnancy (0.73°C) was associated with an odds ratio of 1.02 (95% confidence interval, 1.001.05) for small for gestational age and sex. Reduced fetal growth was associated with elevated ambient temperatures throughout and late in pregnancy, independently of air pollution and other risk factors.